Flexible conducting polymer-based cellulose substrates for on-skin applications - Fu, Xiaoxu (2021)
Flexible electroactive cellulose-based substrates were successfully fabricated via electropolymerization either polypyrrole (PPy) or poly(3,4-ethylenedioxythiophene) (PEDOT) in the presence of sodium dodecyl sulfate (SDS) onto platinum-coated cellulose substrates. Results showed that the conductive polymers were evenly deposited onto the platinum-coated cellulose substrates, respectively without compromising the submicro roughness topography of the substrate. In fact, nanoroughness feature was formed by the deposition of conductive polymers on the individual fibres of the cellulose paper, both of which are highly important in regulating cell adhesion, proliferation and migration. The various electroactive cellulose-based papers exhibited good mechanical and structural properties as well as good cytocompatibility by supporting the attachment and proliferation of immortalized human keratinocytes (HaCaT cells). In addition, copper (Cu2+) and the zinc (Zn2+) ions were proved to be successfully doped into these PPy- and PEDOT-cellulose substrates. The PEDOT resulted in the higher doping of Cu2+ and Zn2+ ions, which was confirmed by the ions release studies. Furthermore, the PEDOT-cellulose substrates exhibited significantly higher mechanical properties, better initial cell attachment and higher electrochemical capacitance as compared to PPy-cellulose substrates. Overall, the results suggested that the PEDOT-cellulose substrates could potentially be a better choice of smart skin dressings, integration interface between skin and artificial devices or implantable electronic materials.